Preliminary Investigation on the Development of a Lower Extremity Exoskeleton for Gait Rehabilitation: A Clinical Consideration - Zahari, Taha; Anwar, P. P. A. Majeed; Mohd Yashim, Wong Paul Tze; Abdul Ghaffar, Abdul Rahman (Engineering and Technology Publishing, 2015)
Gait disorder is the inability of one to maintain balance, assume upright position nor the aptitude to initiate and sustain rhythmic stepping. This form of abnormality may originate from cerebellar disease, stroke, spinal injury, cardiac disease or other general conditions that may instigate such disorder. Studies have shown that one’s mobility may be improved with continuous locomotor activity. Conventional rehabilitation therapy is deemed too laborious as well as cost demanding. Rehabilitation robotics have been explored to address the drawbacks of conventional rehabilitation therapy and the increasing demand for gait rehabilitation. Clinical considerations are often taken for granted amongst other design considerations. This paper attempts a review of the clinical considerations as well as reporting preliminary findings on the development of the iMAMS lower extremity rehabilitation exoskeleton.